2017
DOI: 10.1016/j.gore.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

An ovarian mature cystic teratoma evolving in squamous cell carcinoma: A case report and review of the literature

Abstract: Mature cystic teratomas (MCT), also known as dermoid cysts, are the most common ovarian germ cell tumors and the most common ovarian neoplasms in patients younger than 20 years. Malignant transformation (MT) is a rare complication of MCTs which may occur in 1–2% of the cases. Squamous cell carcinoma (SCC) is the most frequent histology arising from MCTs and its appearance depends on diverse risk factors such as patient's age, the size of the tumor and levels of serum tumor markers. Diagnosis and treatment cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 12 publications
0
41
0
1
Order By: Relevance
“…Age-wise distribution of these cases is mentioned below in table no.1. Name of the study Year of publication Numbers of cases reported Age of occurrence Santwani PM et al [6] 2008 01 40 years Gupta V et al [10] 2009 02 30 years, 65 years Bashyal R et al [3] 2012 03 33 years, 51 years, 60 years Suna Avc1 et al [9] 2012 01 52 years Gupta N et al [4] 2014 01 65 years Ranu Patni [11] 2014 01 53 years Mardi K et al [12] 2014 01 68 years Yarmohammadi H et al [13] 2014 01 48 years Rekhi B et al [14] 2015 12 Median age = 49 years Sharma S et al [1] 2015 01 66 years Abhilasha N et al [8] 2016 10 Median age = 53.5 years Srivastava H et al [2] 2017 01 30 years Goudeli C et al [7] 2017 01 54 years ~ 323 ~ Indulkar ST et al [5] 2018 01 40 years Maharjan S [15] 2019 In our present study, painful enlargement or distension of abdomen is the presenting complaint of the patient herself. Similar complaints have been reported in other case studies also like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Santwani PM et al [6] , etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-wise distribution of these cases is mentioned below in table no.1. Name of the study Year of publication Numbers of cases reported Age of occurrence Santwani PM et al [6] 2008 01 40 years Gupta V et al [10] 2009 02 30 years, 65 years Bashyal R et al [3] 2012 03 33 years, 51 years, 60 years Suna Avc1 et al [9] 2012 01 52 years Gupta N et al [4] 2014 01 65 years Ranu Patni [11] 2014 01 53 years Mardi K et al [12] 2014 01 68 years Yarmohammadi H et al [13] 2014 01 48 years Rekhi B et al [14] 2015 12 Median age = 49 years Sharma S et al [1] 2015 01 66 years Abhilasha N et al [8] 2016 10 Median age = 53.5 years Srivastava H et al [2] 2017 01 30 years Goudeli C et al [7] 2017 01 54 years ~ 323 ~ Indulkar ST et al [5] 2018 01 40 years Maharjan S [15] 2019 In our present study, painful enlargement or distension of abdomen is the presenting complaint of the patient herself. Similar complaints have been reported in other case studies also like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Santwani PM et al [6] , etc.…”
Section: Discussionmentioning
confidence: 99%
“…(e.g. Goudeli C et al [7] ) Yarmohammadi H et al [13] reported a similar case presented with complaints of nausea, non-bloody nonbilious vomiting, diarrhoea, abdominal cramps & night sweats with final diagnosis of small bowel obstruction done by tumor itself. Indulkar ST et al [5] reported a similar case of 40 years old female who presented with complaints of acute abdominal pain and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In at least a quarter of all cases, MCT are asymptomatic and discovered accidentally on a routine pelvic examination, imaging, or during surgery (20). If it causes symptoms, the most common symptom of ovarian MCT is lower abdomen pain, which occurs in nearly half of the patients (9).…”
Section: Symptomsmentioning
confidence: 99%
“…Mature cystic teratoma of ovary (MCTO) is a common tumour among young adult females accounting for around 20% of all ovarian tumours [1,2]. It is relatively rare in children below 12 years of age.…”
Section: Introductionmentioning
confidence: 99%